Cultivating students character: the role of zapin pecah dua belas dance from Pelalawan Riau Province in higher education learning - Evadila, Evadila; Cahyono, Agus; Endraswara, Suwardi; Kurniati, Fatia (Institut Seni Indonesia Surakarta, 2024)
This research investigates the impact of Zapin Pecah Dua Belas Dance on student character education in Riau Malay Dance III (Zapin) lectures seen from the learning process, practice, and elements in traditional dance. Zapin Pecah Dua Belas Dance is a traditional dance originating from Pelalawan, Riau Province. In addition, this research was also conducted to find and describe the process of learning traditional dance in higher education in the formation of student character. The research method uses an interpretative qualitative method with a single case study. The data source of this research consists of several sources, namely through observation, interviews, and literature study. The triangulation method is used as a technique to test the validity of data from these various data sources. The research findings show that learning Zapin Pecah Dua Belas traditional dance can enrich the learner's experience and on the other hand train intelligence and sensitivity through understanding the character of local wisdom contained in traditional dance. Learning Zapin Pecah Dua Belas dance as a traditional dance and dance that is danced in groups fosters the characters: cooperation, discipline, creativity, confidence, mutual cooperation, friendship, effective communication, and responsibility. This research explains the importance of incorporating traditional dance practices, in this case Zapin Pecah Dua Belas Dance, as a local culture into higher education, because this affects the development of students' character as learners.